EDUCATION TO THE FIELD INVESTMENTS ATTRACTION TO DO - Amirov T.M. (American Journals, 2023)
Current in the day countries of the economy development and integration , qualified and competent to personnel has been of demand increased to go as a result education field efficient development and to the field investments active attraction reach important importance occupation is doing Developed countries education field active respectively by developing growing up is coming In our article education field in development abroad experience , developed countries education to the field attraction being carried out investments, them attraction doer factors , them development ways about thought we walk With that together studied data education to the system apply and to practice current reach ways about info giving let 's go.
Keywords: Investment, education system, study, education to the field attraction done investments, foreign education investments.